PEMBERDAYAAN CHILDREN’S VOICES MELALUI PENGELOLAAN READING BOX DIGITAL BERBASIS PHOTOVOICE AND RUANG TERBUKA HIJAU DI DUSUN SAMPARAN, BANTUL, D.I.YOGYAKARTA - Rochmiyati, Siti; Luky, Tiasari; Rezkita, Shanta (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
This community service (PkM) scheme provides services aligned with research findings from a team that received money from the Directorate of Research and Community Service (DRPM) in 2017. The Personal Cooperative Model with Reading Box and Education Fund Management Institution (LPDP) was undertaken in 2022. The significance of community service (PkM) represents an effort to respond to Industrial Revolution 4.0, which emphasizes a green economy that promotes environmental friendliness with green open spaces as a vehicle for children's literacy. Children's voices, combined with their propensity for taking selfies, generate Photovoice, which can be used in the Reading Box. This PkM aims to develop children's voices through photovoice-based digital reading boxes and green open spaces in Samparan Hamlet, Bantul, D.I.Yogyakarta. The method applied is community-based research. The work steps begin with 1) Initiation, which involves addressing local community members and identifying needs (by observation and questionnaires), 2) Socialization with a digital reading box (RBD). 3) Children design an RBD garden with a living barn, pharmacy, and stall, and Ketamansiswaan lessons inspire gorgeous flowers. 4) Photovoice stage: Children photograph the RBD garden's intriguing contents. 5) Literacy stage for children's voices in the RBD garden, in which children narrate the outcomes of their photographs by creating drawings, rhymes, descriptive texts, or methods. Finally, plans for reflection, evaluation, and follow-up are implemented. The activity resulted in 95% of children completing the phases of the activity, children being able to use gadgets responsibly, and children incorporating environmentally sensitive characters. — Pengabdian kepada masyarakat (PkM) ini merupakan Pengabdian berbasis hasil research yang dilakukan oleh tim dengan pendanaan DRPM (2017): Model Personal Cooperative dengan Reading Box dan LPDP (2022): Kolaborasi Dosen-Mahasiswa-Guru dalam Pengembangan Reading Box Digital Berbasis Karakter dalam Pembelajaran di SMP. Urgensi PkM ini dalam rangka menanggapi Revin 4.0 menuju society 5.0 berbasis green economy yang menitikberatkan ramah lingkungan dengan ruang terbuka hijau sebagai wahana berliterasi bagi anak-anak. Children’s voices dan kegemaran anak berselfie menghasilkan Photovoice dapat dimanfaatkan dalam Reading Box. Tujuan PkM ini adalah Menumbuhkan Children’s Voices melalui Reading Box Digital Berbasis Photovoice dan Ruang Terbuka Hijau di Dusun Samparan, Bantul, D.I.Yogyakarta. Metode yang digunakan community based research. Langkah kerja dimulai dengan 1) Tahap inisiasi melalui pendekatan warga masyarakat setempat dan identifikasi kebutuhan (observasi dan angket), 2) Tahap Sosialisasi reading box digital (RBD), 3) anak membuat RBD garden berisi lumbung hidup, apotik hidup, warung hidup, dan bungaku indah berbasis ajaran Tamansiswa, 4) Tahap Photovoice: anak-anak memfoto isi RBD garden yang menarik, 5) Tahap Children’s voices berliterasi di RBD garden yaitu anak mendeskripsikan hasil fotonya dengan membuat gambar, puisi, menyusun teks deskripsi atau prosedur. Terakhir, dilakukan refleksi, evaluasi dan rencana tindak lanjut. Hasil kegiatan yang dicapai adalah 90% anak mampu melaksanakan tahapan kegiatan dengan baik, anak mampu menggunakan gadget dengan bijak dan menerapkan karakter peduli lingkungan.